Variabilidad espacial de la humedad y las fracciones granulométricas en un suelo inceptisol en Machala, provincia de El Oro - Aguilar Sarango, Maria Jose (Machala : Universidad Técnica de Machala, 2020)
The variability of the physical properties of the soils is spatial, the inceptisols because they are in continuous development contain greater variability than more evolved soils. The variation generally depends on the type of soil and the property to be analyzed. By knowing the spatial variability of humidity, it allows us to propose improvements in the efficient use of the water resource in order to obtain a good profitability in agricultural production and with less environmental impact. In view of the fact that the spatial variability of the soil affects the distribution in the water profile, the soil moisture analysis and the relationship with some of the physical properties in an inceptisol soil were performed with the objective of studying the behavior of the soil. Usable humidity based on the granulometric fraction and density supported by a multivariate analysis of certain physical properties through the maps of the spatial distribution of physical attributes to see their spatial variability in the Finca "La Flor" (Machala, Ecuador) dedicated to banana production. Among the main problems caused by low soil productivity is the incorrect execution of agricultural management practices, which causes the deterioration of physical properties, which are important because they regulate the movement of water within the soil and its Evaluation and characterization are helpful to program solutions to problems of compaction, drainage, fertility and low productivity. Soil along with factors such as water-plant are an important key to the development and productivity of banana cultivation because the soil is the main water supplier for the plants due to its large storage capacity and the direct relationship it has with the ability of the plant to remove a part of the water in the soil. Soil moisture is a major role in the behavior of physical properties because substances are transported through it. In the area of the investigation, the planimetric survey of the farm was carried out with a GPS, the geographic information was processed in the AutoCAD 2017 software using an 80 x80 grid, obtaining three sampling points where test pits were made with stairs at a distance of 0m , 3m, 6m, 9m and 12m located on the "x" axis and the "y" axis with 2 soil depths of 0-25 and 25-50 cm, in order to obtain a total of 58 samples to determine physical properties of the soil such as: texture, bulk density, real density, organic matter content, pH, porosity, electrical conductivity and moisture content. The samples were processed using the methodology of the protocols in the soil laboratory located in the Faculty of Agricultural Sciences of the Technical University of Machala. With the data obtained, parameters of central tendency, dispersion and distribution were estimated in the IBM SPSS STATICS 22 software, where the statistical analysis of main components indicates 73.12% of the total variance. This conformed three main components, where the first CP obtained a higher correlation coefficient for sand, silt and clay, while porosity; Gives; MO and HA in PC 2 and 3 respectively, this method allows us to appreciate the behavior of the variables. A geo-statistical analysis was performed using the Arcmap version 10.3 (2014) software using the semivariogram parameters for interpolation by the kriging method to design spatial variability maps of the physical properties of the soil, which provide important information for farm management and future decision making.
La variabilidad de las propiedades físicas de los suelos es espacial, los inceptisoles debido a que están en continuo desarrollo contienen mayor variabilidad que suelos más evolucionados. La variación depende generalmente del tipo de suelo y la propiedad a analizar. Al conocer la variabilidad espacial de la humedad, permite plantear mejoras en el uso eficiente del recurso agua para así obtener una buena rentabilidad en la producción agrícola y con menor impacto ambiental. En visto de que la variabilidad espacial del suelo afecta la distribución en el perfil del agua se realizó el análisis de la humedad del suelo y la relación con algunas de las propiedades físicas en un suelo de orden inceptisol con el objetivo de estudiar el comportamiento de la humedad aprovechable en base a la fracción granulométrica y densidad efectuando un análisis multivariado de ciertas propiedades físicas a través de los mapas del kriggeado de la distribución espacial de los atributos físicos para ver su variabilidad espacial en la Finca “La Flor” (Machala, Ecuador) dedicada a la producción de banano.Con este objeto se analizo, los principales problemas que ocasiona la baja productividad del suelo por la ejecución incorrecta de las prácticas de manejo agrícola, que provoca el deterioro de las propiedades físicas, importantes debido a que regulan el movimiento del agua dentro del suelo y su evaluación y caracterización son de gran ayuda para programar soluciones a problemas de compactación, riego, drenajes y nutrición de la planta. El suelo junto y sus relaciones agua-planta son clave importante para el desarrollo y la productividad del cultivo de banano debido a que el suelo es el principal suministrador de agua para las plantas por su gran capacidad de almacenamiento y la relación directa que tiene con la capacidad de la planta para remover una parte del agua en el suelo, por lo se efectuó esta investigación en la que se analizó el comportamiento de las propiedades físicas en el proceso de almacenamiento del agua en el suelo en todos los sectores de la finca. Para cumplir con los objetivos planteados se efectuó el levantamiento planimétrico de la finca, con un GPS, la información geográfica se la procesó en el software AutoCAD 2017 usando una grilla 80 x80 obteniendo tres puntos de muestreo donde se realizaron calicatas con escalinata a una distancia de 0m, 3m, 6m, 9m y 12 m localizadas en el eje de “x” y el eje “y” , en los estratos de 0-25 y 25-50 cm de profundidad, con la finalidad de obtener un total de 54 muestras para determinar propiedades físicas del suelo como: textura, densidad aparente, densidad real, contenido de materia orgánica, pH, porosidad, conductividad eléctrica y el contenido de humedad. Las muestras fueron procesadas usando la metodología de los protocolos en el laboratorio de suelos ubicado en la Facultad de Ciencias Agropecuarias de la Universidad Técnica de Machala. Con los datos obtenidos se estimó parámetros de tendencia central, dispersión y distribución en el software IBM SPSS STATICS 22 donde el análisis estadístico de componente principales indica 73,12 % de la varianza total. Esto conformó tres componentes principales, donde el primer CP se obtuvo un mayor coeficiente de correlación para arena, limo y arcilla, mientras que porosidad; Da; MO y HA en los CP 2 y 3 respectivamente, este método nos permite apreciar el comportamiento de las variables. Se realizó un análisis geo estadístico utilizando el software Arcmap versión 10.3 (2014) utilizando los parámetros del semivariograma para la interpolación por el método del kriging para el diseño de mapas de variabilidad espacial de las propiedades físicas del suelo, los cuales proveen de información importante para el manejo de la finca y futuras tomas de decisiones.
Keywords: HUMEDAD; SUELO; ESTADÍSTICA; VARIABILIDAD